Study of motivation to practice PSA in school context: Report of motivational style and self-determination - Djennad , Djamal; Ikiouane , Mourad (sports creativity, 2025)
The objective of This study is to détermine the profile and the nature of the motivation to practice PSA in school context, as well as the index of self-determination. It is also a question of verifying the motivational style used by teachers during their psycho-pedagogical intervention, and lastly, studying the Relationship between the perceived motivational style and the level of motivation. In order to do so, we opted for the theory of self-determination as the theoretical basis of the study, in order to be able to explain the different types of self-determined motivations, moreover the link existing between these constructs and the motivational style perceived by the students. The data were collected using the motivation in sport scale (EMS) and the perceived motivational style scale (SMP) from (120) students aged between 12 and 15 years of the middle cycle "CEM Ighil Ouazoug »Located in Bejaia. The results obtained in this study show that: the nature of motivation to practice sports in a school context is characterized by a high level of self-determination (27.87), the perceived motivational style is more oriented towards autonomy. On the other hand, we did not record a significant correlation between the motivational style oriented towards autonomy and the index of self-determination (r = 0.06) and the style oriented towards control (r = -0.03)